Новые таксоны наездников рода сhorebus (hymenoptera, braconidae, alysiinae) - Перепечаенко, В.Л. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Описан Pentalexis, subgen. n. (типовой вид C. (P.) mysteriosus, sp. n.) из рода Сhorebus Haliday. Новый подрод сходен с Phaenolexis Forster, отличаясь от других подродов сочетанием 5-зубых мандибул, глазами, значительно сближенными у вентрального края лица и слабо опушенными глазами. Описаны Chorebus (Pentalexis) mysteriosus, sp. n. из Забайкалья (Россия) и C. (Phaeno-lexis) scythicus, sp. n. из Украины. Описана аберрантная форма C. (Stiphrocera) sp. Pentalexis, subgen. n. (type species C. (P.) mysteriosus, sp. n.) of the genus Ñhorebus Haliday is escribed. The new subgenus shows affinities with Phaenolexis Fo rster, differing from the other subgenera by the combination of 5-toothed mandibles, eyes approximated in the ventral part of face and weakly pubescent eyes. Chorebus (Pentalexis) mysteriosus, sp. n. from Transbaikalia (Russia) and C. (Phaenolexis) scythicus, sp. n. from Ukraine are described. An abberant form of C. (Stiphrocera) sp. Is described.